ENERGY OF AN INTUITIONISTIC FUZZY GRAPH - Praba, B.; Chandrasekaran, V.M.; Deepa, G. (Italian Journal of Pure and Applied Mathematics, 2014)
In this paper, the concept of energy of fuzzy graph is extended to the energy of an intuitionistic fuzzy graph. We have defined the adjacency matrix of an intuitionistic fuzzy graph and the energy of an intuitionistic fuzzy graph is defined in terms of its adjacency matrix. These concepts are illustrated with real time example. The lower and upper bound for the energy of an intuitionistic fuzzy graph are also derived.